A process for the treatment of olive mill waste waters by immobilized cells. - A. Amhajji; M. Faid; M. ElYachioui (Grasas y Aceites, 2005)
Mould strains were immobilized on sawdust from woods as a solid material for the treatment of Olive Mill Waste (OMW) waters. Assays were carried out in flasks. The treatment process was monitored by physico-chemical determinations including pH, polyphenols and COD, which were followed up during the incubation time. In parallel the chemical inhibitory activity of OMW was confirmed biologically by the determination of some microorganisms in the medium including the plate count, yeasts and lactic acid bacteria. Results indicated that the polyphenol degradation level was 87 %. The COD was also reduced by 60 %. The pH of the effluent increased from 4.5 to 6.6. The microbial profiles showed their best growth during the treatment period indicating a removal of the inhibitory activities from the OMW waters. The growth patterns of all microorganism groups were similar and could reach high levels in the effluent.